An envelope approach to tournament design - Christian Ewerhart (University of Zurich, Department of Economics, 2014)
Optimal rank-order tournaments have traditionally been studied using a first-order approach. The present analysis relies instead on the construction of an "upper envelope" over all incentive compatibility conditions. lt turns out that the first-order approach is not innocuous. For example, in contrast to the traditional understanding, tournaments may be dominated by piece rates even if workers are risk-neutral. The paper also offers a strikingly simple characterization of the optimal tournament for quadratic costs and CARA utility, as well as an extension to large tournaments.
Keywords: C62; D86; L23; 330; Rank-order tournaments; first-order approach; envelope theorem